High‐Energy‐Density Magnesium‐Air Battery Based on Dual‐Layer Gel Electrolyte. (9th June 2021) - Li, Luhe; Chen, Hao; He, Er; Wang, Lie; Ye, Tingting; Lu, Jiang; Jiao, Yiding; Wang, Jiacheng; Gao, Rui; Peng, Huisheng; Zhang, Ye
Abstract: Mg‐air batteries are explored as the next‐generation power systems for wearable and implantable electronics as they could work stably in neutral electrolytes and are also biocompatible. However, high corrosion rate and low utilization of Mg anode largely impair the performance of Mg‐air battery with low discharge voltage, poor specific capacity and low energy density. Here, to the best of our knowledge, we first report a dual‐layer gel electrolyte to simultaneously solve the above two problems by preventing the corrosion of Mg anode and the production of dense passive layer, respectively. The resulting Mg‐air batteries produced an average specific capacity of 2190 mAh g −1 based on the total Mg anode (99.3 % utilization rate of Mg anode) and energy density of 2282 Wh kg −1 based on the total anode and air electrode, both of which are the highest among the reported Mg‐air batteries. Besides, our Mg‐air batteries could be made into a fiber shape, and they were flexible to work stably under various deformations such as bending and twisting. Abstract : A dual‐layer gel electrolyte was designed to simultaneously prevent the corrosion of Mg anode and production of the dense passive layer in a Mg‐air battery. The resulting Mg‐air battery exhibited a specific capacity of 2190 mAh g −1 based on total anodic weight and an energy density of 2282 Wh kg −1 based on the total weight of anode and air electrode. It was further made into a fiber shape with high flexibility.